PHONE APPLICATION BASED WIRELESS APPLICATION PROTOCOL (WAP) - Berrie Nugraha Adiwinata; Sunarto Usna (Jurnal Sistem Informasi, 2001)
WAP mobile phone sales in Indonesia is quite high, evidenced by a recent survey saidnearly about 5% of mobile phone users in Indonesia is a mobile phone using WAPtechnology. For those who always need accurate information and quick. WAPtechnology a ride on a GSM network still has weaknesses such as an expensiveaccess costs. But do not close the possibility that one day we will get a perfect WAPphones.